2015
DOI: 10.1007/s40641-015-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Change on Mangrove Forests

Abstract: Mangrove forests have survived a number of catastrophic climate events since first appearing along the shores of the Tethys Sea during the late Cretaceous-Early Tertiary. The existence of mangrove peat deposits worldwide attests to past episodes of local and regional extinction, primarily in response to abrupt, rapid rises in sea level. Occupying a harsh margin between land and sea, most mangrove plants and associated organisms are predisposed to be either resilient or resistant to most environmental change. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
210
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(254 citation statements)
references
References 89 publications
4
210
0
12
Order By: Relevance
“…For mangroves in the Indo-Pacific, Lovelock et al (2015) reported that 69% of their sites were not building surface elevations at rates that equaled or exceeded sea-level rise. Additional losses are expected to occur as a result of coastal squeeze, in regions where sea level rises and pushes mangroves landward into areas where the lack of suitable space (e.g., due to natural or anthropogenic barriers) hampers up-slope dispersal and subsequent establishment (Alongi, 2015). Alongi (2015) predicted that the impact of climate change would be felt most acutely by mangroves along arid coasts as salinities increase, freshwater supplies decrease, and critical temperature thresholds are reached.…”
Section: Potential Mangrove Losses Due To Climate Changementioning
confidence: 99%
“…For mangroves in the Indo-Pacific, Lovelock et al (2015) reported that 69% of their sites were not building surface elevations at rates that equaled or exceeded sea-level rise. Additional losses are expected to occur as a result of coastal squeeze, in regions where sea level rises and pushes mangroves landward into areas where the lack of suitable space (e.g., due to natural or anthropogenic barriers) hampers up-slope dispersal and subsequent establishment (Alongi, 2015). Alongi (2015) predicted that the impact of climate change would be felt most acutely by mangroves along arid coasts as salinities increase, freshwater supplies decrease, and critical temperature thresholds are reached.…”
Section: Potential Mangrove Losses Due To Climate Changementioning
confidence: 99%
“…Increased temperatures result in faster mangrove growth and greater mangrove diversity. Field data from mangrove surveys around the world [204,[206][207][208] indicate contemporary poleward (latitudinal) expansion due to the global increase in sea surface temperature [208].…”
Section: Mangrovesmentioning
confidence: 99%
“…Subsidence, a decreasing in sediment transport from the Ganges and other rivers to the sea due to damming, and rising sea level, resulted in a dramatic decline in mangroves growing on islands, particularly in the central and eastern sectors of the Sundarbans (Rahu et al 2012). In other river deltas, sea level rise, storms, and cyclones enhanced subsidence and declines in sediment supply, resulting in a landward migration of mangroves but with a net contraction (Alongi 2015).…”
mentioning
confidence: 99%